2003
DOI: 10.1038/nm833
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of virus transmission to macaque monkeys by a vaginally applied monoclonal antibody to HIV-1 gp120

Abstract: A topical microbicide reduces the probability of virus transmission when applied to the vagina or rectum of a person at risk of sexually acquiring HIV-1 infection. An effective microbicide could significantly reduce the global spread of HIV-1, particularly if women were able to use it covertly to protect themselves. A microbicide could target the incoming virus and either permanently inactivate it or reduce its infectivity, or it could block receptors on susceptible cells near the sites of transmission. We des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
337
1
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 438 publications
(349 citation statements)
references
References 25 publications
9
337
1
1
Order By: Relevance
“…Topical application of MAb b12 has been shown to protect macaques from infection after vaginal challenge with SHIV, which supports the potential use of antibodies for topical prevention of HIV-1 transmission (82). Further studies are needed to establish whether the identified VHH would have preventive effects in vivo.…”
Section: Discussionmentioning
confidence: 84%
“…Topical application of MAb b12 has been shown to protect macaques from infection after vaginal challenge with SHIV, which supports the potential use of antibodies for topical prevention of HIV-1 transmission (82). Further studies are needed to establish whether the identified VHH would have preventive effects in vivo.…”
Section: Discussionmentioning
confidence: 84%
“…Preferred agents for this use inhibit early steps in the HIV cycle, like attachment, fusion, and entry, to prevent integration of the viral genome into chromosomal DNA (53). Successful use of entry inhibitors to block vaginal transmission of HIV in rhesus macaques has been reported (54)(55)(56). It has been shown recently that C34 can completely block HIV infection of Langerhans cells when continuously present before, during, and after exposure of cells to virus, but only partially when the peptide is not present during incubation with virus (51).…”
Section: C34-chol Is the Most Potent Hiv Fi Known To Datementioning
confidence: 99%
“…Second, passive immunization with 2F5 Abs protected macaques from a mucosal challenge (17,18). Similarly, vaginal application of the gp120-directed b12 Ab was highly effective in protecting monkeys from a vaginal challenge (19). Third, anti-HIV-1 secretory IgA, isolated from mucosal secretions of infected individuals, can block transcytosis of HIV-1 and infection of CD4 ϩ cells ex vivo (20,21) and the neutralization potential of these Abs was greater than the paired IgGs (21).…”
mentioning
confidence: 99%